2015
DOI: 10.1093/icesjms/fsv139
|View full text |Cite
|
Sign up to set email alerts
|

Seascape genetics of saithe (Pollachius virens) across the North Atlantic using single nucleotide polymorphisms

Abstract: The identification of isolated populations in widely distributed marine species is often impeded by low levels of genetic differentiation. However, modern genetic approaches now allow for the efficient detection of potentially large numbers of novel genetic variations, thereby improving the power to identify biologically meaningful management units. To investigate the genetic structuring of saithe (Pollachius virens L.), we applied seascape genetic approaches to 131 single nucleotide polymorphism loci genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 39 publications
4
21
0
Order By: Relevance
“…Quantitative integration of population genetics with marine ecology, oceanography or geography, known as seascape genetics, is a rapidly growing field that allows powerful insight into the complexities of marine connectivity beyond traditional genetic models (reviewed in Selkoe et al., ). Seascape genetics studies to date have largely focussed on species with pelagic larval dispersal, particularly fish (Liggins, Treml, Possingham, & Riginos,; Saenz‐Agudelo et al., ; Saha et al., ; Selkoe et al., ), corals (Foster et al., ; Thomas et al., ) and other invertebrates (Benestan et al., ; Giles, Saenz‐Agudelo, Hussey, Ravasi, & Berumen, ; Selkoe et al., ; Silva & Gardner, ; Teske, Sandoval‐Castillo, Van Sebille, Waters, & Beheregaray, ). With the exception of kelp stands (Alberto et al., ; Fraser, Thiel, Spencer, & Waters, ), relatively little attention has been paid to groups with non‐larval propagules, such as mangroves.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative integration of population genetics with marine ecology, oceanography or geography, known as seascape genetics, is a rapidly growing field that allows powerful insight into the complexities of marine connectivity beyond traditional genetic models (reviewed in Selkoe et al., ). Seascape genetics studies to date have largely focussed on species with pelagic larval dispersal, particularly fish (Liggins, Treml, Possingham, & Riginos,; Saenz‐Agudelo et al., ; Saha et al., ; Selkoe et al., ), corals (Foster et al., ; Thomas et al., ) and other invertebrates (Benestan et al., ; Giles, Saenz‐Agudelo, Hussey, Ravasi, & Berumen, ; Selkoe et al., ; Silva & Gardner, ; Teske, Sandoval‐Castillo, Van Sebille, Waters, & Beheregaray, ). With the exception of kelp stands (Alberto et al., ; Fraser, Thiel, Spencer, & Waters, ), relatively little attention has been paid to groups with non‐larval propagules, such as mangroves.…”
Section: Introductionmentioning
confidence: 99%
“…Saha et al . () published a broadscale account of the genetic structure of P. virens throughout its range using seascape genetics. They found that four broad genetic clusters could be distinguished; the Barents Sea, the central north‐east Atlantic, Rockall and Canada.…”
Section: Introductionmentioning
confidence: 99%
“…The estimates of genetic differentiation reported on S. bibarbatus by Gunawickrama et al () may have been inflated by the presence of private mtDNA haplotypes in high frequencies in some sample groups and relatively small sample sizes (ranged 20–49 individuals). But the greater differentiation in the mtDNA could also reflect possible higher site fidelity for females than males as shown for saithe by both nuclear markers (Saha et al, ) and mtDNA (Eríksson & Árnason, ). We did not record sex in our samples and could therefore not test this hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…The reproductive behavior of S. bibarbatus could add to the complexity of its genetic structuring. For example, if the sex of mature fish were known, we could have tested if there was site fidelity in females compared to males, which has been observed for Saithe in the North Atlantic (Saha et al, ). Furthermore, the presence of alternative reproductive tactics in S. bibarbatus (Salvanes et al, ; Seivåg et al, ) and eggs attached to a substrate and cared for by territorial males (Skrypzeck et al, ), could be taken as evidence for low connectivity between some of the sampling groups.…”
Section: Discussionmentioning
confidence: 99%